HUBUNGAN SELF ASSESMENT SYSTEM DENGAN TINGKAT KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA ARGAMAKMUR PROVINSI BENGKULU - Karona Cahya Susena; Suwarni Suwarni; Joko Widianto (UNIVED Press, 2018)
The purpose of this study was to determine the relationship of tax collection with the self assessment system with the level of taxpayer compliance in the Kantor Pelayanan Pajak Pratama Argamakmur Provinsi Bengkulu. The analytical methods used are Average Distribution, Spearman Rank Correlation and Hypothesis Testing. Based on the results of the analysis that has been done, it is known that the value of rho (count) is 0.755 in the interval of interpretation of the correlation of 0.600-0.799, a strong level of relationship. This means that the relationship between the self assessment system and the level of tax compliance at the Kantor Pelayanan Pajak Pratama Argamakmur Provinsi Bengkulu is strong and the value of rho (count) is 0.755> 0.364 rho (table) so that Ho is rejected and Ha is accepted, meaning that there is a significant relationship between the self assessment system with taxpayer compliance level at the Kantor Pelayanan Pajak Pratama Argamakmur Provinsi Bengkulu.